Phosphatidylethanolamine Synthesis in Castor Bean Endosperm - Sparace, Salvatore A. (1981)
Phosphatidylethanolamine synthesis by CDP-ethanolamine:1,2-diacylglycerol ethanolaminephosphotransferase (EC 2.7.8.1) from the endoplasmic reticulum of castor bean (Ricinus communis L. var. Hale) endosperm was characterized. The Michaelis-Menten constant of the enzyme for CDP-ethanolamine was approximately 8.0 micromolar. The pH optimum was 6.5 and a divalent cation was an absolute requirement for activity, with Mg(2+) giving the greatest stimulation at 3 millimolar. Sulfhydryl reagents variously affected enzyme activity. No discernible differences were detected between the responses of the ethanolaminephosphotransferase and CDP-choline:1,2-diacylglycerol cholinephosphotransferase (EC 2.7.8.2) to a variety of treatments. CDP-choline and CDP-ethanolamine were competitive inhibitors of the ethanolaminephosphotransferase and cholinephosphotransferase reactions, respectively.